Mining Business Pursuant to “Ius Regale Montanorum” in the 14th Century - Petra Jánošíková (Journal on European History of Law)
The paper deals with the forms of mining business in the 14th century, its assumptions, and importance within the context of than legal regulation based on interpretation of sources and their political-economical analysis.